Exploring the impact path of school connectedness on student development through cultivating students’ social-emotional skills - Yukai Wei; Xinyi Wang (PLoS ONE, 2026)
Based on OECD’s Survey on Social and Emotional Skills (SSES) Asian data (n = 23560), this study examines the pathways through which school connectedness relates to students’ positive development using structural equation modeling. The findings reveal that school connectedness predicts student positive development through serial effect of interpersonal skills and emotion regulation skills. School connectedness is associated with social-emotional skills (student engaging with others). These two social-emotional skills both predict students’ positive development. Student-classmate relationship and perceived relationship with teachers contribute to school connectedness. Energy, stress resistance, and optimism are important social-emotional skills. The outcomes are primarily reflected in positive emotions at school and students’ school engagement. The study elucidates the internal mechanism through which the school environment predicts students’ development via a sequence of social-emotional skills, offering meaningful implications for optimizing school connectedness and cultivating student’s social-emotional skills.